PENGARUH UANG BEREDAR DAN NILAI TUKAR RUPIAH (KRUS) TERHADAP INFLASI (PERIODE JANUARI 2015-DESEMBER 2019) - Adim, Abd (Jurnal Ekonomi Syariah Darussalam, 2021)
The money supply is one of the macroeconomic indicators that the monetary authority oversees. the development of the money supply has a direct relationship and influence on the development of economic activity, especially in Indonesia. the method of adding money to the economy will increase the problem of increasing the price level of goods and services, so that inflation is affected. If the money supply is very low, an economic downturn will occur. It contains money and assets that can be quickly converted into cash. M1 focuses purely on the role of money as a medium of exchange. Currency and demand deposits or Narrow Money, which have the characteristic of being able to be used as a means of payment at any time or at any time if desired, are not bound by time in their use.